RNA sequencing-based profiling of differentially expressed microRNAs in endothelial cells from offspring of hypertensive pregnancies: a preliminary study - Mohd Isa, Nurul Iffah; Abdull Sukor, Aslah Nabilah; Syafruddin, Saiful Effendi; Ahmad, Mohd Faizal; Zainal Abidin, Shahidee; Mokhtar, Mohd Helmy; Ugusman, Azizah; Hamid, Adila A. (Frontiers in Molecular Biosciences, 2025)
Offspring of mothers with hypertensive disorders of pregnancy (HDP) are at increased risk of developing endothelial dysfunction and cardiovascular disease (CVD) in adulthood. MicroRNAs (miRNAs), as key regulators of endothelial cells, may contribute to the early onset of endothelial dysfunction. However, there are limited studies characterizing the miRNA profile of endothelial cells in offspring of HDP. Therefore, this study aims to determine the miRNA expression profile of human umbilical vein endothelial cells (HUVECs) isolated from the offspring of HDP. HUVECs were obtained from both normal and hypertensive umbilical cords. RNA sequencing analysis revealed that eight miRNAs were significantly upregulated in HUVECs from HDP (p < 0.05). The target genes of these miRNAs were then predicted using four databases: miRDB, TargetScan, DIANA-microT-CDS, and miRWalk. Gene ontology, pathway enrichment, and protein-protein interaction network analyses revealed that the target genes of these miRNAs are involved in cellular functions and pathways related to angiogenesis and cellular senescence, which may contribute to endothelial dysfunction and CVD. The most significantly upregulated miRNA, hsa-miR-196a-5p expression was then validated through stem-loop RT-qPCR where its expression was significantly upregulated in hypertensive HUVEC by 6-fold as compared to normal HUVEC (p < 0.01). These findings offer insights into the role of miRNAs in the development of CVD in offspring exposed to HDP, highlighting their potential as predictive markers and therapeutic targets in the future.